Optimizing the lithotripsy timing after drainage of the upper urinary tract in patients with urolithiasis and obstructive uropathy - A. I. Khotko; D. N. Khotko; V. M. Popkov; A. I. Tarasenk (Вестник урологии, 2021)
Introduction. Timely unresolved upper urinary tract (UUT) obstruction in patients with infection can cause severe complications, such as sepsis, pyonephrosis and even death. There are no clear recommendations regarding the methods and timing of drainage. At the same time, this issue is still the subject of discussion in publications of recent years.Purpose of the study. To optimize the timing of lithotripsy after drainage of the UUT in patients with urolithiasis and obstructive uropathy (OU).Materials and methods. At the first stage, 90 patients with OU caused by the stone of the ureteropelvic junction underwent drainage of the UUT using a percutaneous nephrostomy. Subsequently, percutaneous nephrolithotripsy (PNLT) was performed at various times after drainage. The level of inflammatory markers (IL-8) and profibrotic factor (MCP-1) in the urine was determined. The calculated concentrations of urinary biomarkers were normalized by the level of urinary creatinine. Urine sampling for the analysis was carried out during and after the PCN placement (nephrostomy urine) 7 days later, and then once weekly before surgery. The coefficient K was calculated using a patented formula to evaluate the process of kidney remodeling. Urine sampling was performed for culture to determine the bacterial spectrum and antibiotic sensitivity.Results. The values of K ≤ 1.85 were observed in 11 patients of the group with OU (12.2%), K > 1.85 in 79 (87.8%) by day 21. The values of K ≤ 1.85 were achieved in 70 patients (88.6%) by day 28 and 4 patients (80.0%) by day 35. PNLT was performed on 21 days in patients with K ≤ 1.85 (11 patients), no complications were noted in the postoperative period., PNLT was performed in patients with K ≤ 1.85 (70 patients) by day 28, exacerbation of pyelonephritis and the development of chronic kidney disease were not noted. Six patients with values of K ˃ 1.85 underwent PNLT by day 28. In the postoperative period, all patients had an exacerbation of calculous pyelonephritis, 50% had a decrease in glomerular filtration rate within 3 months after surgery. The bacteria in urine were detected in 55 (61.0%) patients. Escherichia coli (63.0%), Proteus mirabilis (18.0%), Enterococcus faecalis (14.5%), Streptococcus haemolyticus (2.5%) were identified most often.Conclusion. The use of the developed remodeling index allows optimizing the surgery timing and minimizing the development of complications during the postoperative period. The presence of bacteria is associated with a long process of renal parenchymal remodeling.